Phyllodes diversipalpus resurrected from taxonomic extinction (Lepidoptera: Erebidae) - Alberto Zilli (Fragmenta entomologica, 2020)
Morphological evidence supporting the validity of Phyllodes diversipalpus sp. rev. from New Guinea is provided. This species is only superficially similar to P. eyndhovii and P. staudingeri and, having been associated with either of the two, was eventually wrongly subsumed under the latter.